2018
DOI: 10.19087/jveteriner.2018.19.1.109
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Limfosit, Monosit, dan Basofil pada Sapi Bali yang Digembalakan di Tempat Pembuangan Akhir Sampah Kota Denpasar (THE ELEVATION LEVEL OF LIMPHOCYTE, MONOCYTE, AND BASOPHIL ON BALI CATTLE GRAZING AT WASTE DISPOSAL CITY OF DENPASAR)

Abstract: The Bali cattles that grazing at Denpasar city waste disposal need to examined for their healthy to keep the quality of beef production. The aim of this research to determine the hematologic profile of Bali cattle was grazing at waste disposel in Denpasar. The data obtained is expected to provide an initial ekspretion of the general health-related to productivity. Studies using nine female of Bali cattle weighing 250-300 kg, aged 2-3 years. Research using quantitative methods by means of surveys and research l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Based on interviews with farmers, we revealed that the Aceh cattle used in the study were fed only on grass without the addition of concentrate. Ariana et al (2018) also state that nutritional factors can cause changes in the blood profiles. The erythrocyte index includes the mean corpuscular volume (MCV) that shows the average volume of one erythrocyte cell, the mean corpuscular hemoglobin (MCH) that describe the amount of hemoglobin contained in red blood cells, and the mean corpuscular hemoglobin content (MCHC) that represent the amount of hemoglobin concentration in the MCH red blood cells (Cunningham, 2002).…”
Section: Advances In Animal and Veterinary Sciences January 2020 | Vomentioning
confidence: 99%
See 1 more Smart Citation
“…Based on interviews with farmers, we revealed that the Aceh cattle used in the study were fed only on grass without the addition of concentrate. Ariana et al (2018) also state that nutritional factors can cause changes in the blood profiles. The erythrocyte index includes the mean corpuscular volume (MCV) that shows the average volume of one erythrocyte cell, the mean corpuscular hemoglobin (MCH) that describe the amount of hemoglobin contained in red blood cells, and the mean corpuscular hemoglobin content (MCHC) that represent the amount of hemoglobin concentration in the MCH red blood cells (Cunningham, 2002).…”
Section: Advances In Animal and Veterinary Sciences January 2020 | Vomentioning
confidence: 99%
“…The high ratio of neutrophils can demonstrate stress in cattle compared to lymphocytes (N/L), in addition to high levels of stress hormones in the blood (Gomes et al, 2011;Anton et al, 2016). Variations in the hematological profile can provide information related to oxygen transport, the sensitivity of cattle to stress, and is an indication of animal Advances in Animal and Veterinary Sciences January 2020 | Volume 8 | Issue 1 | Page 112 tolerance to heat and environmental stress (Ariana et al, 2018;Gomes et al, 2011).…”
Section: Advances In Animal and Veterinary Sciences January 2020 | Vomentioning
confidence: 99%
“…Penanganan ternak babi sebelum dipotong, seperti manajemen nutrisi, iklim atau temperatur, ketakutan, kelelahan atau gerakan yang berlebihan dapat memengaruhi performa, metabolisme otot pascamati dan data fisiologis, seperti profil hematologi (Ariana et al, 2018). Dalam manajemen pemeliharaan ternak babi, pakan masih menduduki biaya paling tinggi (70-80%).…”
Section: Pendahuluanunclassified
“…Good physical and chemical qualities of meat are the main requirements for its acceptance by consumers. Handling pigs before slaughter, such as nutrition, climate or temperature, fatigue, and excessive movement, can affect post-mortem muscle metabolism, meat quality, and blood profile [1 , 11 , 19] . In raising pigs, feed costs are still the highest (70%–80%), and the problem causes breeders to always look for alternative feed sources that are less expensive but do not reduce their nutritional value [12] .…”
Section: Introductionmentioning
confidence: 99%